2011
DOI: 10.5688/ajpe75464
|View full text |Cite
|
Sign up to set email alerts
|

Student Stress in a Three-Year Doctor of Pharmacy Program Using a Mastery Learning Educational Model

Abstract: Objective. To identify stress and stress-relieving mechanisms among second-year pharmacy students in a 3-year doctor of pharmacy (PharmD) program using a Mastery Learning Educational Model and to compare findings with those from a 4-year program. Methods. Second-year PharmD students in a 3-year program were asked to complete a series of questionnaires including the Perceived Stress Scale (PSS) regarding stress and stress-relieving activities.Results. The average PSS score for the 3-year PharmD cohort was signi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
27
2

Year Published

2011
2011
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 47 publications
(32 citation statements)
references
References 15 publications
3
27
2
Order By: Relevance
“…29,30 It is concerning that at least 33% of the students at three of the campuses used alcohol to manage stress. This is analogous with other research that has linked the role of student stress to high tobacco, 31 alcohol, 8,9,32 and drug use. 8,33 Oliver et al demonstrated that more hazardous alcohol consumption was prevalent among pharmacy students at the main campus than students in the branch campus.…”
Section: Discussionsupporting
confidence: 81%
See 3 more Smart Citations
“…29,30 It is concerning that at least 33% of the students at three of the campuses used alcohol to manage stress. This is analogous with other research that has linked the role of student stress to high tobacco, 31 alcohol, 8,9,32 and drug use. 8,33 Oliver et al demonstrated that more hazardous alcohol consumption was prevalent among pharmacy students at the main campus than students in the branch campus.…”
Section: Discussionsupporting
confidence: 81%
“…This is analogous with other research that has linked the role of student stress to high tobacco, 31 alcohol, 8,9,32 and drug use. 8,33 Oliver et al demonstrated that more hazardous alcohol consumption was prevalent among pharmacy students at the main campus than students in the branch campus. 9 Alcohol may be the drug of choice for coping with workload stress, and schools should develop workshops or programs that show students other ways to manage stress and encourage students to seek out these resources.…”
Section: Discussionsupporting
confidence: 81%
See 2 more Smart Citations
“…For example, one college investigated student burnout in its new distance learning program 39 and another assessed perceived stress of students in a 3-year doctor of pharmacy program. 40 Students' attainment of nonacademic curricular and course outcomes can be assessed in a variety of ways and levels in the classroom, during clinical training, and postgraduation. Professional training presents challenges in instilling traditional values of altruism, responsibility, accountability, and other professional attributes.…”
Section: Data Collection About Performancementioning
confidence: 99%